The brand-personality of three categories of drinks in Australia - Liang, Johan; Lee, Wai (School of Marketing, Curtin Business School, 2010)
This study focuses on the 42 traits of brand personality (Aaker 1997) of nine drink brands spanning across three drink segments - fizzy drink, mineral water and energy drink, and measure the congruity of the brands' personalities (five dimension) to the consumer (drinker) of those brands. Based on the results, excitement is the point-of-parity for fizzy drink and energy drink while sincerity is the point-of-parity for mineral water. Other four brand personalities can become the point-of-difference for each brand in each drink category. Using these results, a better understanding of brand personalities of each brand in customer minds can be used to improve marketing communication more effectively and give the right message to the right target market. Future research should be done on such fields and sectors as restaurants, food, other fast moving consumer goods and the like and include a wider sample audience, spanning across different geographical borders. Implication for conceptual, methodological and managerial also discussed in this study.